EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINKING ALOUD PAIRS PROBLEM SOLVING (TAPPS) DAN TEAMS ASSISTED INDIVIDUALIZATION (TAI) DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI ALJABAR DITINJAU DARI GAYA BELAJAR SISWA - Ulfa, Marchamah; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of research was to know the effect of learning models on mathematics learning achievement viewed from the student learning style. The learning models compared were TAPPS, TAI and classical with scientific approach. This research used the quasi experimental method. The population was the students of junior high school in Surakarta regency on academic year 2014/2015. The tecnique of taking sample was stratified cluster random sampling. The size of the sample was 291 students. The instruments used were examination test and learning styles test. The proposed hypothesis were analyzed using the unbalanced two-way analysis of variance. The conclusions were as follows. 1) TAPPS with scientific approach have better mathematics achievement than TAI and classical with scientific approach, TAI and classical with scientific approach have the same achievement. 2) auditory students have better mathematics achievement than visual and kinesthetic students, visual and kinesthetic students have the same achievement. 3) In TAPPS with scientific approach, auditory students have better achievement than visual students, kinesthetic studentshave the same achievement as visual and auditory students. In TAI with scientific approach, auditory students have better achievement than visual and kinesthetic students, visual and kinesthetic students have the same achievement. In classical with scientific approach, auditory students have the same achievement as visual and kinesthetic students, visual students have better achievement than kinesthetic students. 4) In visual students, TAPPS with scientific approach have the same achievement as TAI and classical with scientific approach, classical with scientific approach have better achievement than TAI with scientific approach. In auditorial students, TAPPS and TAI with scientific approach have the same achievement, TAPPS and TAI with scientific approach have better achievement than classical with scientific approach. In kinesthetic students, TAI with scientific approach have the same achievement as TAPPS and classical with scientific approach, TAPPS with scientific approach have better achievement than classical with scientific approach.Key words: TAPPS, TAI, classical, scientific approach, learning styles, achievement of learning.